Sulfadiazine advanced oxidizing-degradation: Defects generation by boosting electron transfer at interfaces of Co-Cu LDH catalysts. Issue 6 (December 2022) - Guo, Xiaoxi; Wu, Hongyang; Wang, Huanhuan; Li, Bolan; Meng, Bo; Li, Rui; Chen, Jiali; Han, Yifan
Abstract: A comprehensive study of advanced oxidation was conducted over Co-Cu layered double hydroxide (LDH) catalysts, while the Co-Cu interaction mechanism at interfaces as well as oxygen vacancies (Ov ) on the production of hydroxyl radicals (OH) were studied. Cu could promote the oxidation of Co 2+ by depressing the formation of β-Co(OH)2 and replacing Co sites in octahedral environment in α-Co(OH)2 . A Co4 Cu1 LDH catalyst showed the highest sulfadiazine (SDZ) removal efficiency of 93.7%. The reaction mechanism was assumed on the base of kinetics study of SDZ removal. The formation of Co-O-Cu oxo-bridge in MO6 surroundings can enhance the generation of ameliorated Ov, which improves the formation of surface hydroxyl for H2 O2 adsorption by boosting electron-transfer rate under the Co-Cu interaction at interfaces. This study paves a new way to the Fenton-Like catalysts R&D, especially orientating to the remediation of non-biodegradable organic wastes from pharmaceutical industry. Graphical Abstract: Plausible mechanism of the Fenton-like reaction. ga1 Highlights: Oxygen vacancies in Co-Cu LDH enhancing the yielding of OH in Fenton-like reaction. Mono-Co/Cu catalyst with high Ov density benefiting H2 O2 adsorption and OH generation. Co-Cu interaction boosting electron transfer for defects generation in Co-Cu LDH catalyst. Co4 Cu1 catalyst with improved LDH structure showed 79.2% removal for sulfadiazine within 1 h. Kinetics mechanism of oxidative degradation for SDZ elucidated the contribution of surface defects.